P.2.20 Epidemic of bladder cancer in japanese male workers exposed mainly to ortho-toluidine. (April 2019) - Nakano, Makiko; Omae, Kazuyuki; Eitaki, Yoko; Iwasawa, Satoko; Fukai, Kota; Yoshioka, Noriyuki; Tanaka, Shigeru; Koda, Shigeki; Takebayashi, Toru
Abstract : Background: In 2012, ortho-toluidine (OT) was listed as a Group 1 carcinogen by the International Agency for Research on Cancer, based on epidemiologic observations in workers co-exposed to OT and aromatic amines. Between 2014 and 2017, 10 cases of bladder cancer (BC) were identified in Japanese males working at two plants of the same company manufacturing intermediates of organic dyes and pigments. Objective: To describe the features of the BC epidemic at the plants. Methods: We conducted a cross-sectional study of 76 OT and/or aromatic amine-exposed workers including the 10 BC cases at the plants in 2017. The co-exposed aromatic amines were para-toluidine, ortho-anisidine, aniline, 2, 4-dimethylaniline, and/or ortho-chloroaniline. Details of each worker's job-site histories were obtained from the company records. Past medical symptoms and histories were checked in physician interviews. The subjects were divided into the BC group (n=10) and the non-BC group (n=66) and compared. No quantitative exposure data were available. The surrogate level of exposure to each aromatic amine was calculated as the summed job-weight-month in each process in each job-year. Results: The mean ages of the non-BC and BC groups were 50 and 56 years and the durations of employment were 23 and 20 years, respectively. The smoking rate in both groups was 80%. Significantly higher rates of gross hematuria (70%) and cystitis (70%) were identified in the BC group's past medical histories. In the BC group, the surrogate levels of exposure to OT were higher than those of exposures to other aromatic amines. The surrogate levels were high in the job processes of filtering, rinsing, drying and packing products. Conclusions: The subjects with BC were associated with a high surrogate level of exposure to OT. OT-exposed workers with past histories of gross hematuria and cystitis need a careful follow-up.